COSMOGENIC ARCHITECTURE: A STUDY OF YOKA SARA’S DESIGN APPROACH ON ANTONIO BLANCO’S HOTEL - Dea Aulia Widyaevan (Dimensi: Journal of Architecture and Built Environment, 2018)
The Antonio Blanco’s hotel design by Balinese base architect Yoka Sara been design to represent the extension of Antonio Blanco’s museum in Ubud Bali. Although this design only achieves in a preliminary stage, the design approach in which Yoka Sara offer to interpret the style of Balinese contemporary, reflect the idea of Cosmogenic Architecture by Charles Jencks. In his book “Architecture of The Jumping Universe”  Jencks stated about how in the postmodern era, the architect should have the freedom to use architecture as a language. The nature of architecture has been identified with a definition of the universe through contemporary sciences. This paper tries to reveal the cosmogenic value in Antonio Blanco’s hotel approach by analogizing the architectural vocabulary into the linguistic system as Jencks mention in his book “The Language of Postmodern Architecture”. The issue of genius loci concept of cosmos also discusses to be coherent with the idea of cosmos in contemporary science. In related to architecture design, and a new way to re-define cosmos in contemporary Balinese architecture